Research Transformation through Multi-Paradigm Methodology Training for Undergraduate Accounting Students - Triyuwono, Iwan; Purwanti, Lilik; Prakoso, Aryo; Ibrahim, Melinda (Journal of Universal Community Empowerment Provision, 2024)
The exploration of scientific disciplines is not only monodisciplinary but has developed into transdisciplinary, even multidisciplinary. Faculty of Economics and Business Universitas Brawijaya is a producer of scientific research, but unfortunately undergraduate students still have limitations related to multi-paradigm research methodology. The implementation of this Multiparadigm Methodology Training activity aims to provide an understanding of alternative methodologies in research using qualitative methods for accounting undergraduate students. The main focus is to increase students' understanding and awareness of Multiparadigm Research Methodology. the techniques used in this PKM activity are pre-test, material presentation, post-test, and question and answer discussion. The method for assessing the success of this activity uses different tests from the pretest and post-test results. The data results will be tested using a paired sample t test with the object of this PKM research, namely undergraduate accounting students of FEB Universitas Brawijaya who attended the activity. The results of the t-test show that (1) descriptive analysis of the average value shows an increase from 59.2 to 94.1; (2) The statistical test results show that there is a significant difference between the pre-test and post-test, which indicates that there is a significant effect after the treatment. The statistical test results confirm that there is a significant effect on the participants' scores before and after receiving the treatment, as well as a significant increase in the participants' average scores, which shows that the exposure to the materials provided is quite effective in improving their understanding in Qualitative Methods Training. The implication of this research is that participants have a broader insight into muti-paradigm methodology and can apply it in research.